Plasticity of NK cells in Cancer - Corvino, Dillon; Kumar, Ananthi; Bald, Tobias (Frontiers in Immunology, 2022)
Natural killer (NK) cells are crucial to various facets of human immunity and function through direct cytotoxicity or via orchestration of the broader immune response. NK cells exist across a wide range of functional and phenotypic identities. Murine and human studies have revealed that NK cells possess substantial plasticity and can alter their function and phenotype in response to external signals. NK cells also play a critical role in tumor immunity and form the basis for many emerging immunotherapeutic approaches. NK cells can directly target and lyse malignant cells with their inherent cytotoxic capabilities. In addition to direct targeting of malignant cells, certain subsets of NK cells can mediate antibody-dependent cellular cytotoxicity (ADCC) which is integral to some forms of immune checkpoint-blockade immunotherapy. Another important feature of various NK cell subsets is to co-ordinate anti-tumor immune responses by recruiting adaptive and innate leukocytes. However, given the diverse range of NK cell identities it is unsurprising that both pro-tumoral and anti-tumoral NK cell subsets have been described. Here, NK cell subsets have been shown to promote angiogenesis, drive inflammation and immune evasion in the tumor microenvironment. To date, the signals that drive tumor-infiltrating NK cells towards the acquisition of a pro- or anti-tumoral function are poorly understood. The notion of tumor microenvironment-driven NK cell plasticity has substantial implications for the development of NK-based immunotherapeutics. This review will highlight the current knowledge of NK cell plasticity pertaining to the tumor microenvironment. Additionally, this review will pose critical and relevant questions that need to be addressed by the field in coming years.